Strategi Transformasi Digital dan Dampaknya Terhadap Loyalitas Nasabah pada PT Bank Muamalat Indonesia Cabang Kendari - Murniati Murniati; Murni Nia; Yuyun Saputri (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the digital transformation strategy implemented and examine its impact on customer loyalty at PT Bank Muamalat Indonesia Kendari Branch. This research uses a qualitative approach with a descriptive research type. Data collection techniques were carried out through observation, in-depth interviews, and documentation involving branch management, operational and information technology service staff, and customers who use digital services. The data analysis technique used includes data reduction, data presentation, and conclusion drawing. The results show that the digital transformation strategy is carried out through three main stages, namely environmental analysis, service planning and implementation, and continuous evaluation and control. The forms of digital services developed include Muamalat DIN, Internet Banking, and QRIS. The implementation of this strategy has proven to provide convenience, speed, and transaction security while adhering to sharia principles, thus having a positive impact on satisfaction and the formation of customer loyalty. This is reflected in indicators of satisfaction with service benefits, usage loyalty, prioritizing services, and willingness to recommend to others